Photoperiod management in dairy herd - K.N. WADHWANI, R.J. MODI, M.M. ISLAM (Indian Journal of Animal Production and Management, 2019)
Photoperiod management deals with manipulation of light and dark exposure to the animals during 24hours duration. Shifting of cow from short day (8 hrs. of light) photoperiod (SDPP) to long day (16 - 18hrs. of light) photoperiod (LDPP) improved performance of dairy animals. Light stimulates photoreceptorcells of retina which subsequently relay inhibitory signal to pineal gland for melatonin secretion via retinohypothalamic tract through a series of endogenous process. Melatonin secretes at night and duration ofsecretion vary inversely with day length. Melatonin secretion from pineal gland further influences secretionof number of other hormones like prolactin (PRL), gonadotropins and IGF-I. Alterations in these circulatinghormones influence growth, reproduction, lactation and immunity of dairy animals. Photo periodic responsewas more with fluorescent, metal halide, high pressure sodium lighting. The recommended level of lightfor the cow was 15 foot candle (162 lux) at 1m (3’) height from the stall floor. The 30 (close house) and45 foot candle (open house) produce the good effect. The separation distance between two lights shouldbe 1.5 times more than mounting height (14 – 35 ft) depending on type of sheds. The optimum CRI oflight for calf house was 80. The recommended illumination level for milking parlour was 50 foot candles.Duration of exposure to photoperiod directly affects growth of calves and heifers, as well as the mammarytissue growth in heifers. Exposure to LDPP during the growth phase results larger and leaner animals atmaturity with greater mammary parenchymal growth and these effects are associated with greater yield infirst calver. Extending photoperiod (4 hrs.) using 160 lux light during winter season resulted in better growthrate and early onset of puberty in buffalo heifers. Proliferation of mammary cells was better in SDPP drycows as compared to LDPP. Cows reared on LDPP during early lactation produced more milk (8 to 10%)than on natural photoperiod. The effect of LDPP developed gradually and significantly after 3 - 4 weeks ofexposure. However, there is no carryover effect of photoperiod on milk production. LDPP produced moremilk yield may be due to elevated level of prolactin, growth hormone and IGF-I. Dry cow on SDPP for entiredry period produces more milk (up to 3 kg) along with protein and fat in next lactation. SDPP also increasedfeed intake (more than 1 kg) and improved the immunity in advanced pregnant dry cows. Duration of daylength during autumn and winter is generally shorter, but cattle and buffaloes when exposed to LDPPshow significant improvement of reproduction. Improved reproduction in cows reared under LDPP may beassociated with increased circulating Ca, P, vitamin D and A, total protein, hemoglobin, erythrocytes andγ-globulins. Heifers reared under SDPP had increased lymphocyte proliferation and enhanced neutrophilfunction than those reared under LDPP. SDPP exposure to dry cows improves immune status, uterine andudder health immediately during post partum period. Somatic cell counts also reduced in cows exposedto SDPP during dry period in contrast to cows under LDPP.Thus, proper manipulation of photoperiod improved lactating animal performance especially in terms ofmilk, reproduction and health of animals.